Kajian Analisis Struktur Gedung 2D dengan Ketidakberaturan Vertikal Menggunakan Metode Nonlinear Pushover - Kumar, Sharent; Hasibuan, Samsul Abdul Rahman Sidik (Sultra Civil Engineering Journal (SCiEJ), 2025)
Multi-story buildings with vertical irregularities often experience uneven load distribution, which can affect the structural performance under lateral loads, particularly seismic forces. Vertical irregularities, such as varying column and beam dimensions between floors, can lead to significant increases in displacement and deformation on the upper floors compared to the lower floors. Therefore, it is crucial to evaluate the impact of vertical irregularities on the structure's behavior to ensure building safety. This study aims to analyze the impact of vertical irregularity on the behavior of multi-story buildings using the nonlinear pushover method. The analysis was performed using SAP2000 software to assess the structural capacity to withstand lateral loads, particularly seismic loads. The results show a significant linear relationship between story displacement and lateral forces (R² = 0.8898), as well as the impact of vertical irregularities that increase story drift and story drift ratio on the upper floors. The increase in story drift ratio exceeding the earthquake design standard limits may affect the stability of the structure. Furthermore, this study reveals that vertical irregularity can cause significant differences in forces on columns and beams between the lower and upper floors, increasing the risk of structural failure. Based on these findings, it is recommended to consider vertical irregularities in the design of multi-story buildings, accounting for a more uniform distribution of forces throughout the building to ensure structural resilience against seismic loads.